Strategi Pemasaran Perguruan Tinggi Swasta di Kabupaten Sleman Yogyakarta Berbasis Rangsangan Pemasaran - Andriya Risdwiyanto; Yuli Kurniyati (Universitas Proklamasi 45 Yogyakarta, 2015)
This study is a replication of research conducted Risdwiyanto and Dharmmesta (2001), which seeks to develop a concept of higher education services based on the wishes of potential customers. This study examined the effect of marketing mix models to the selection of private universities (PTS) in Sleman, Yogyakarta. Sleman Regency is one of the areas in the Province of Yogyakarta Special Region which has a lot of colleges. The model in this study based on marketing mix consisting of seven marketing stimuli, namely product, price, place, promotion, people, physical evidence, and process. This study aimed to analyze the influence of factors of marketing stimuli to the selection of private universities in Sleman Yogyakarta by prospective students and know the significance rank of the influence of each marketing stimuli factor. This study uses the Focus Group Discussion (FGD) to collect preliminary data and surveys to obtain primary data. By using the 142 students of XII class of High School (SMA) in Sleman as samples, this study proves that the replication model used may indicate a significant influence of marketing stimuli on the election of PTS. The important contribution of this research is the development model of the influence of marketing stimuli factors on the selection of PTS that can be used as a basis for decision making PTS marketing strategy.